2010
DOI: 10.1074/jbc.m110.151209
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase LSD1 Regulates Adipogenesis

Abstract: Epigenetic mechanisms, in particular the enzymatic modification of histones, are a crucial element of cell differentiation, a regulated process that allows a precursor cell basically to turn into a different cell type while maintaining the same genetic equipment. We have previously described that the promoters of adipogenic genes display significant levels of dimethylation at the Lys 4 of histone H3 (H3K4) in preadipocytes, where these genes are still silenced, thus maintaining the chromatin of the precursor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
128
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 44 publications
12
128
1
Order By: Relevance
“…Previous studies have shown that H3K9me2 is enriched on the promoters of C/EBP␣ and PPAR␥ in preadipocytes and decreases with the increase of H3K4me3 during differentiation (29,46). But it is poorly understood whether H3K9me3 contributes to the repression of C/EBP␣ in the early stages of differentiation and whether Suv39h1 has any function during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that H3K9me2 is enriched on the promoters of C/EBP␣ and PPAR␥ in preadipocytes and decreases with the increase of H3K4me3 during differentiation (29,46). But it is poorly understood whether H3K9me3 contributes to the repression of C/EBP␣ in the early stages of differentiation and whether Suv39h1 has any function during adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pax-transactivationdomain-interacting protein  (PTIP, officially known as PAXIP1) regulates the expression of both C/EBP and PPARg by controlling recruitment of the histone 3 lysine 4 (H3K4) methyltransferase MLL4, as well as DNA polymerase II, to their promoters (Cho et al, 2009). In addition, the lysine-specific histone demethylase 1A (KDM1A, also known as LSD1) and the H3K9 methyltransferase SET domain, bifurcated 1 (SETDB1) exhibit opposing effects by promoting and inhibiting adipogenesis, respectively (Musri et al, 2010). It has been proposed that SETDB1 maintains the promoter for the gene encoding C/EBP in a silent state, but that recruitment of LSD1 increases upon differentiation, permitting induction of C/EBP expression (Musri et al, 2010).…”
Section: Histone Modificationmentioning
confidence: 99%
“…In addition, the lysine-specific histone demethylase 1A (KDM1A, also known as LSD1) and the H3K9 methyltransferase SET domain, bifurcated 1 (SETDB1) exhibit opposing effects by promoting and inhibiting adipogenesis, respectively (Musri et al, 2010). It has been proposed that SETDB1 maintains the promoter for the gene encoding C/EBP in a silent state, but that recruitment of LSD1 increases upon differentiation, permitting induction of C/EBP expression (Musri et al, 2010).…”
Section: Histone Modificationmentioning
confidence: 99%
“…There are two major types of HMTs, lysine-specific, which can be SET (Su(var)3-9, Enhancer of Zeste, Trithorax) domain containing or non-SET domain containing. Contrary to a relatively well defined histone methylating system, histone demethylation machinery is not well studied; LSD1, a lysine-specific histone demethylase, specifically removes methyl group from H3K4me and H3K9me [36,37].…”
Section: Epigenetics and Gene Regulationmentioning
confidence: 99%